Utopias and architecture - Coleman, Nathaniel, 1961-; ebrary, Inc. (London : Routledge, Taylor & Francis Group, 2005)
Utopian thought, though commonly characterized as projecting a future without a past, depends on golden models for re-invention of what is. Through a detailed and innovative re-assessment of the work of three architects who sought to represent a utopian content in their work, and a consideration of the thoughts of a range of leading writers, Coleman offers the reader a unique perspective of idealism in architectural design. With unparalleled depth and focus of vision on the work of Le Corbusier, Louis I Kahn and Aldo van Eyck, this book persuasively challenges predominant assumptions in current architectural discourse, forging a new approach to the invention of welcoming built environments and transcending the limitations of both the postmodern and hyper-modern stance and orthodox modernist architecture.
Introduction : utopias and architectures? -- Conceptualizing utopias -- Architecture and orientation -- Situating utopias -- Real fictions -- Varieties of architectural utopias -- Post war possibilities -- Optimistic architectures -- Le Corbusier's monastic ideal -- The life within -- Fairy tales and golden dust -- Kahn and Salk's challenge to dualistic thinking -- Aldo van Eyck's utopian discipline -- Story of another idea -- The unthinkability of utopia -- Into the present
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: moderní architektura; architektonický design; utopie; teorie architektury; architektura -- filozofické aspekty; modern architecture; architectural design; utopias; theory of architecture; architecture -- philosophical aspects; monografie; e-knihy online; monographs; e-books online